1999
DOI: 10.1007/s001270050106
|View full text |Cite
|
Sign up to set email alerts
|

Life stress, social support and psychological distress in late adolescence: a longitudinal study

Abstract: Questionnaire data from 211 adolescents and follow-up data recorded 18 months later were employed to test main effects and stress-buffering effects of negative life events, on-going stressors and social support from family and friends on mental health. Negative life events, change from baseline level of on-going adversities and social support all contributed significantly to subsequent symptom scores, although negative life events only reached borderline significance among boys. There was evidence in favour of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
3
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 25 publications
7
68
3
3
Order By: Relevance
“…A tendency among respondents towards answering questions in general as either yes or no on the questionnaire could potentially produce biased estimates. 36 However, there is little reason to believe that women who tend to report severe sexual violence also tend to report more somatic symptoms, and our findings are consistent with other studies showing a relationship between violence exposure and somatization. Somatic symptoms are more common than exposure to violence, overreporting symptoms would tend to underestimate the impact of violence exposure on somatic symptoms and diseases.…”
Section: Discussionsupporting
confidence: 89%
“…A tendency among respondents towards answering questions in general as either yes or no on the questionnaire could potentially produce biased estimates. 36 However, there is little reason to believe that women who tend to report severe sexual violence also tend to report more somatic symptoms, and our findings are consistent with other studies showing a relationship between violence exposure and somatization. Somatic symptoms are more common than exposure to violence, overreporting symptoms would tend to underestimate the impact of violence exposure on somatic symptoms and diseases.…”
Section: Discussionsupporting
confidence: 89%
“…Further, a study by Desjardins and Leadbeater (2011) revealed that emotional support from fathers reduced the association between adolescents' relational victimization and depressive symptoms. Finally, an 18-month longitudinal study demonstrated that the harmful effects of negative life events were reduced by parental support (Ystgaard et al, 1999). Hammen (2005) pointed out that multiple models explaining the development and maintenance of depression, such as the cognitive stress-vulnerability model of depression (Beck, 1976) and the self-esteem vulnerability model (Brown & Harris, 1978), are conceptualized similarly to the stress-buffer model.…”
Section: Models Of the Associations Between Supportive Relationships mentioning
confidence: 99%
“…High levels of well-being were found to be associated with low life stress in studies by Weir (1978a, 1978b), Burt, Cohen and Bjorck (1988), Cauce, Hannan and Sargeant, (1992), Dumont, and Provost (1999), Frye and Goodman (2000), Gore and Aseltine (1995), Herman-Stahl and Petersen (1996), Southhall and Roberts (2002) Spence, Sheffield and Donovan (2002), Windle (1992), and Ystgaard, Tambs and Dalgard (1999). High levels of well-being have been found to be associated with a variety of personal strengths including an internal locus of control (Cauce, Hannan and Sargeant, 1992); self-efficacy (Herman-Stahl and Petersen, 1996); self-esteem (Dumont, and Provost, 1999;Southhall and Roberts, 2002);…”
Section: Discussionmentioning
confidence: 95%
“…High levels of well-being have been found to be associated with greater social resources including high levels of social support Weir, 1978a, 1978b;Cauce, Hannan and Sargeant, 1992;Gore and Aseltine, 1995;Windle, 1992;and Ystgaard, Tambs and Dalgard, 1999) and a positive family climate (Burt, Cohen and Bjorck, 1988), A structural equation model which explained the relationships among the variables in these profiles was developed. In this model increased personal strengths was associated with better subjective well-being and fewer stressful life events; and increased social resources was associated with better task-focused coping.…”
Section: Discussionmentioning
confidence: 99%